Inhibition of ascorbate peroxidase by salicylic acid and 2,6-dichloroisonicotinic acid, two inducers of plant defense responses. - Durner, J (1995)
In recent years, it has become apparent that salicylic acid (SA) plays an important role in plant defense responses to pathogen attack. Previous studies have suggested that one of SA's mechanisms of action is the inhibition of catalase, resulting in elevated levels of H2O2, which activate defense-related genes. Here we demonstrate that SA also inhibits ascorbate peroxoidase (APX), the other key enzyme for scavenging H2O2. The synthetic inducer of defense responses, 2,6-dichloroisonicotinic acid (INA), was also found to be an effective inhibitor of APX. In the presence of 750 microM ascorbic acid (AsA), substrate-dependent IC50 values of 78 microM and 95 microM were obtained for SA and INA, respectively. Furthermore, the ability of SA analogues to block APX activity correlated with their ability to induce defense-related genes in tobacco and enhance resistance to tobacco mosaic virus. Inhibition of APX by SA appears to be reversible, thus differing from the time-dependent, irreversible inactivation by suicide substrates such as p-aminophenol. In contrast to APX, the guaiacol-utilizing peroxidases, which participate in the synthesis and crosslinking of cell wall components as part of the defense response, are not inhibited by SA or INA. The inhibition of both catalase and APX, but not guaiacol peroxidases, supports the hypothesis that SA-induced defense responses are mediated, in part, through elevated H2O2 levels or coupled perturbations of the cellular redox state.